Software metrics in software engineering / Nur Ida Aniza Rusli - Rusli, Nur Ida Aniza (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Software metrics are defined as numerical measurements that are used to quantify the properties and characteristics of software systems. These metrics are essential in software engineering as they help in assessing software performance, monitoring software productivity, predicting development costs, sizing the development team, and many more. Having a knowledge of software metrics and their utilization can facilitate effective management in the software development process.